Iron Oxide-Silica Core-Shell Nanoparticles Functionalized with Essential Oils for Antimicrobial Therapies - Cristina Chircov; Maria-Florentina Matei; Ionela Andreea Neacșu; Bogdan Stefan Vasile; Ovidiu-Cristian Oprea; Alexa-Maria Croitoru; Roxana-Doina Trușcă; Ecaterina Andronescu; Ionuț Sorescu; Florica Bărbuceanu (MDPI AG, 2021)
Recent years have witnessed a tremendous interest in the use of essential oils in biomedical applications due to their intrinsic antimicrobial, antioxidant, and anticancer properties. However, their low aqueous solubility and high volatility compromise their maximum potential, thus requiring the development of efficient supports for their delivery. Hence, this manuscript focuses on developing nanostructured systems based on Fe3O4@SiO2 core-shell nanoparticles and three different types of essential oils, i.e., thyme, rosemary, and basil, to overcome these limitations. Specifically, this work represents a comparative study between co-precipitation and microwave-assisted hydrothermal methods for the synthesis of Fe3O4@SiO2 core-shell nanoparticles. All magnetic samples were characterized by X-ray diffraction (XRD), gas chromatography-mass spectrometry (GC-MS), Fourier-transform infrared spectroscopy (FTIR), dynamic light scattering (DLS), zeta potential, scanning electron microscopy (SEM), transmission electron microscopy (TEM), thermogravimetry and differential scanning calorimetry (TG-DSC), and vibrating sample magnetometry (VSM) to study the impact of the synthesis method on the nanoparticle formation and properties, in terms of crystallinity, purity, size, morphology, stability, and magnetization. Moreover, the antimicrobial properties of the synthesized nanocomposites were assessed through in vitro tests on Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, and Candida albicans. In this manner, this study demonstrated the efficiency of the core-shell nanostructured systems as potential applications in antimicrobial therapies.